PEMBUATAN, UJI FISIKOKIMIA DAN UJI STABILITAS MINYAK KELAPA (Cocos nucifera L.) RENDAH FREE FATTY ACIDS (FFA) DARI LIMBAH KULIT BUAH KELAPA (TESTA) - Ahmad Sairi; Liandhajani Liandhajani; Muhammad Iqbal; Ramadhan Triyandi; Donny Yudha Asmara (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2026)
Coconut (Cocos nucifera L.) is an important commodity for Indonesia’s economy, with testa (coconut seed coat) waste commonly found in traditional markets. A survey in Bandar Lampung revealed daily testa waste production of 13.5–18.0 kg. This study aimed to explore the potential of coconut testa oil through extraction and esterification processes. Extraction was performed using a fat extractor E-500 with n-hexane solvent at heating levels 2, 5, and 8, followed by esterification. The results showed that testa oil contained 1.36% free fatty acids (FFA). Physicochemical analysis using GC-MS demonstrated identical chromatogram peaks between testa oil and Brc oil, with saturated fatty acids bound as triglycerides. The unsaturated fatty acid content in testa oil (0.28%) was slightly higher than in Brc oil (0.27%). Accelerated Shelf Life Test (ASLT) predicted a shelf life of four months for testa oil. In conclusion, coconut testa oil has potential as a vegetable oil source with physicochemical characteristics comparable to Brc oil, although its unsaturated fatty acid content remains relatively low.